There Is No William Blake: @autoblake's Algorithmic Condition. Issue 1 (April 2016) - Whitson, Roger
Abstract : This article examines a Twitterbot I created in the summer of 2013 to automatically tweet lines of poetry that mimic the style of William Blake. What does it mean for a tweet to be Blakean? The question recalls Alan Turing's famous test of artificial intelligence: how do we know when a machine exhibits intelligence? I explore Turing's question with specific reference to the temporal structure of algorithmic loops and branches found in Blake's poetry, the Markov-chain structure used to statistically generate natural language, and the auto-generated lines of poetry produced by my Twitter program. My article takes inspiration from Friedrich Kittler's article "There is No Software, " in which he questions what writing means when automatic processes are increasingly mediating communication online. For me, Blake's poetic syntax enables an analogous exploration in the field of Romantic literary studies: namely how we can understand the meaning of poetry and literature when it is computationally mediated and generated, a situation I call the "algorithmic condition."